Alcohol and Pain: A Translational Review of Preclinical and Clinical Findings to Inform Future Treatment Strategies. (6th January 2020) - Edwards, Scott; Vendruscolo, Leandro F.; Gilpin, Nicholas W.; Wojnar, Marcin; Witkiewitz, Katie
Abstract : Alcohol use disorder (AUD) and chronic pain are enduring and devastating conditions that share an intersecting epidemiology and neurobiology. Chronic alcohol use itself can produce a characteristic painful neuropathy, while the regular analgesic use of alcohol in the context of nociceptive sensitization and heightened affective pain sensitivity may promote negative reinforcement mechanisms that underlie AUD maintenance and progression. The goal of this review was to provide a broad translational framework that communicates research findings spanning preclinical and clinical studies, including a review of genetic, molecular, behavioral, and social mechanisms that facilitate interactions between persistent pain and alcohol use. We also consider recent evidence that will shape future investigations into novel treatment mechanisms for pain in individuals suffering from AUD. Abstract : Alcohol use disorder and chronic pain are both complex and heterogenous conditions with high prevalence and high rates of comorbidity, with both producing devastating social, human, and economic costs. Continued refinement of rodent models and improved insights into how alcohol and chronic pain interact with multiple physiological and psychiatric disease processes in humans will be necessary to propel future research discoveries and treatment avenues.